THE EFFECT OF WORKLOAD ON TURNOVER INTENTION WITH REWARD AS MODERATING VARIABLES AT PT. BUMI MADINAH IHSANY - Maidita (Human Resource Management Studies, 2025)
This study aims to examine the effect of workload on Turnover intention at PT. Bumi Madinah Ihsany and the effect of workload on the level of Turnover intention at PT. Bumi Madinah Ihsany with reward as a moderating variable.. This research is a quantitative study. The population of this study is all employees of PT. Bumi Madinah Ihsany with a total of 51 employees. The sampling technique used is total sampling. Data collection uses a questionnaire with a Likert scale. The analytical tool used is SPSS software with descriptive test analysis techniques, classical assumption tests, multiple regression tests, and hypothesis tests. The results of data processing in this study indicate that there is an influence of workload on turnover intention at PT. Bumi Madinah Ihsany. This indicates that the higher the workload felt by PT. Bumi Madinah Ihsany employees, the higher their turnover intention and rewards do not moderate the influence of workload on turnover intention at PT. Bumi Madinah Ihsany. This indicates that there is no influence or impact given by workload through rewards felt by PT. Bumi Madinah Ihsany employees.